Gender responsive budgeting in Vietnam gender equality in transport. (ASEAN+3 Bond Market Guides, 2019)
Transport is both a key element of national infrastructure and a key to gender equality. Poor investment in gender responsive transport infrastructure makes it more difficult for women to access paid work, for example. This brief by ADB and UN Women introduces gender responsive budgeting and provides recommendations on how to implement it in the transport sector in Viet Nam.